Either Give Me a Reason to Stand or an Opportunity to Sit in VR - Zielasko, Daniel; Riecke, Bernhard E. (SeatedVR: 1st Workshop on Seated Virtual Reality at IEEE VIrtual Reality, 2020)
In this position paper, we want to point, with a little bit of provocation and maybe a pinch of fun, to some grievances of and also chances for today’s pool of (consumer) VR applications concerning the chosen user posture. In our opinion, the user is considered standing or required to stand in too many cases, and transitions between postures are usually entirely unsupported.
Keywords: 2-page conference paper; NSERC DG 2026; Riecke; Riecke_2020; bernhard-riecke; conferencePaper; conferencePapers; daniel-zielasko; locomotion; short conference paper